Coumarin-piperazine derivatives as biologically active compounds - Kinga Ostrowska (Elsevier, 2020)
A number of psychiatric disorders, including anxiety, schizophrenia, Parkinson's disease, depression and others CNS diseases are known to induce defects in the function of neural pathways sustained by the neurotransmitters, like dopamine and serotonin. N-arylpiperazine moiety is important for CNS-activity, particularly for serotonergic and dopaminergic activity. In the scientific literature there are many examples of coumarin-piperazine derivatives, particularly with arylpiperazines linked to a coumarin system via an alkyl liner, which can modulate serotonin, dopamine and adrenergic receptors. Numerous studies have revealed that the inclusion of a piperazine moiety could occasionally provide unexpected improvements in the bioactivity of various biologically active compounds. The piperazine analogs have been shown to have a potent antimicrobial activity and they can also act as BACE-1 inhibitors. On the other hand, arylpiperazines linked to coumarin derivatives have been shown to have antiproliferative activity against leukemia, lung, colon, breast, and prostate tumors. Recently, it has been reported that coumarin-piperazine derivatives exhibit a Fneuroprotective effect by their antioxidant and anti-inflammatory activities and they also show activity as acetylcholinesterase inhibitors and antifilarial activity. In this work we provide a summary of the latest advances in coumarin-related chemistry relevant for biological activity. Keywords: Coumarin, Arylpiperazinyl moiety, Biological activity